Development of a multimedia educational programme for first-time hearing aid users: a participatory design - Ferguson, Melanie A.; Leighton, Paul; Brandreth, Marian; Wharrad, Heather (Taylor & Francis, 2018)
Objective: To develop content for a series of interactive video tutorials (or reusable learning objects, RLOs) for first-time adult hearing aid users, to enhance knowledge of hearing aids and communication. Design: RLO content was based on an electronically-delivered Delphi review, workshops, and iterative peer-review and feedback using a mixed-methods participatory approach. Study sample: An expert panel of 33 hearing healthcare professionals, and workshops involving 32 hearing aid users and 11 audiologists. This ensured that social, emotional and practical experiences of the end-user alongside clinical validity were captured. Results: Content for evidence-based, self-contained RLOs based on pedagogical principles were developed for delivery via DVD for television, PC or internet. Content was developed based on Delphi review statements about essential information that reached consensus (≥90%), visual representations of relevant concepts relating to hearing aids and communication, with iterative peer-review and feedback of content. Conclusions: This participatory approach recognises and involves key stakeholders in the design process to create content for a user-friendly multimedia educational intervention, to supplement the clinical management of first-time hearing aid users. We propose participatory methodologies are used in the development of content for e-learning interventions in hearing-related research and clinical practice.